Tiger, tiger - Caveney, Philip (New York : St. Martin's Press, 1984)
Malaya in the late 1960s was at last casting off the yoke of British colonial rule. But Harry 'Tiger' Sullivan, a retired military officer, had made his career in Malaya for almost two decades had nowhere else to go. Well respected for his distinguished military service, and even more so for his legendary skill in tracking and killing man-eating tigers, Harry Sullivan's life was a comfortable and well-ordered one, until the arrival of Bob Beresford, a brash and handsome Australian. Melissa Tremayne, an eighteen-year-old British expatriate bored with the slow pace of life in Malaya, had always been like the daughter Sullivan never had, but one look at Bob Beresford makes Melissa determined to win his not-so-fatherly affection. The rivalry between the two men intensifies with the sudden appearance of a man-eating tiger, emerging from the jungle at unpredictable intervals to attach and terrorise Malayan villagers. Bob wants the glory of killing the beast, while Melissa is pursuing a different kind of trophy -- Bob himself. Sullivan finds himself drawn into a trial of manhood that he is unwilling to undertake. The tension builds steadily towards a thrilling climax in the Malayan jungle.
A novel of honor and rivalry set in Malaya.
Koleksi Sumbangan : Zainal Abidin Abdul Wahid.
Keywords: English fiction